2015
DOI: 10.1038/srep16176
|View full text |Cite
|
Sign up to set email alerts
|

Ventral tegmental area dopamine and GABA neurons: Physiological properties and expression of mRNA for endocannabinoid biosynthetic elements

Abstract: The ventral tegmental area (VTA) is involved in adaptive reward and motivation processing and is composed of dopamine (DA) and GABA neurons. Defining the elements regulating activity and synaptic plasticity of these cells is critical to understanding mechanisms of reward and addiction. While endocannabinoids (eCBs) that potentially contribute to addiction are known to be involved in synaptic plasticity mechanisms in the VTA, where they are produced is poorly understood. In this study, DA and GABAergic cells we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 91 publications
(138 reference statements)
2
40
0
Order By: Relevance
“…It has become clear that the physiological criteria that were formerly used to identify dopaminergic neurons within the VTA are in fact somewhat misleading, as these “classical” criteria have been shown to not only exclude some DAergic neurons but also to include non-DA neurons (Margolis et al, 2006, 2008b; Lammel et al, 2008; Merrill et al, 2015; but see Chieng et al, 2011). To aid in the identification of DA neurons, most of our experiments were performed in TH-GFP mice (Sawamoto et al, 2001), providing us with an alternate means to identify a population of medial VTA DA neurons that have previously been under-studied (Lammel et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…It has become clear that the physiological criteria that were formerly used to identify dopaminergic neurons within the VTA are in fact somewhat misleading, as these “classical” criteria have been shown to not only exclude some DAergic neurons but also to include non-DA neurons (Margolis et al, 2006, 2008b; Lammel et al, 2008; Merrill et al, 2015; but see Chieng et al, 2011). To aid in the identification of DA neurons, most of our experiments were performed in TH-GFP mice (Sawamoto et al, 2001), providing us with an alternate means to identify a population of medial VTA DA neurons that have previously been under-studied (Lammel et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…3E). Although most GFP-positive neurons co-labeled with an antibody to the GABA synthesizing enzyme GAD67 these cell counts may underestimate the true number of MGE-derived GABAergic interneurons because (i) tissue for these studies was processed from adult mice undergoing various procedures that could impact activity-dependent enzyme levels, and (ii) GAD67 expression was confirmed in only 75% of GFP-expressing cells in studies using GAD67-GFP mice 51 . It has previously been shown that IPSC frequency, a physiological measure of GABA-mediated inhibition, is enhanced 20-40% in regions containing MGE progenitor derived interneurons 11,15,17,38 .…”
Section: Discussionmentioning
confidence: 99%
“…Testing between these possibilities has been challenging in the absence of interneuron-specific molecular markers. Indeed, of the cardinal interneuron markers used to identify and selectively target sub-populations of interneurons in other regions of the brain, most are either not expressed in either the VTA or SNc, or are also expressed by sub-groups of dopamine neurons (e.g., somatostatin, cholecystokinin, vasoactive intestinal peptide, neuropeptide Y, parvalbumin, and calretinin; Hökfelt et al, 1980; Seroogy et al, 1988 , 1989; Rogers, 1992; Isaacs and Jacobowitz, 1994; Liang et al, 1996; Gonzalez-Hernandez and Rodriguez, 2000; Klink et al, 2001; Lein et al, 2007; Olson and Nestler, 2007; Dougalis et al, 2012; Merrill et al, 2015 ). One potential candidate, however, is neuronal nitric oxide synthase (nNOS).…”
Section: Introductionmentioning
confidence: 99%